STRATEGI OPTIMALISASI COMPETITIVE ADVANTAGE UMKM KOTA SEMARANG DI ERA DIGITAL (STUDI KASUS DI CV NEW CITRA) - RACHMADI, MOCH FAIZAL (Jurnal Studi Ekonomi dan Pembangunan, 2025)
This study aims to understand the strategy of optimizing the competitive advantage of MSMEs in Semarang City in the digital era (case study at CV New Citra). The role of Micro, Small and Medium Enterprises (MSMEs) is very central and their contribution to the national economic sector is very high. The level of resilience of MSMEs is also high, especially during the monetary crisis at that time and continues to survive until now. However, the limitations are the lack of marketing strategies, especially in the digital era like today which is less adaptive, the level of competence of Human Resources (HR) is minimal, technology adaptation is still low, innovation and creativity are also not optimal. Therefore, the competitive advantage of an MSME is also not optimal. This research method is descriptive qualitative with data collection techniques being interviews, observations and documentation. Data validity is based on source triangulation with the Miles Huberman technique, namely with data reduction, data presentation and drawing conclusions. The results of the study show that a growth mindset is very important in entrepreneurship. In the marketing mix analysis, it is also a special consideration in the operational business of CV New Citra. Not only about product quality but also price competition, business premises and distribution and promotional media used in optimizing consumer engagement. The concept of sustainable entrepreneurship as a sustainable business approach by optimizing the digital technology adaptation model is able to increase the effectiveness, efficiency, productivity and profitability of the business at CV New Citra.